Evaluating Ventures Fast and Slow: Sensemaking, Intuition, and Deliberation in Entrepreneurial Resource Provision Decisions. (July 2023) - Fisher, Greg; Neubert, Emily
We examine the decision process of individuals evaluating whether to support an entrepreneurial endeavor. Such decisions are made by individuals under conditions of ambiguity and equivocality. Therefore, it is nearly impossible for resource providers to adopt a purely rational evaluative process in assessing a venture. Building on insights from sensemaking and social and cognitive psychology, we elaborate a theoretical model combining sensemaking, intuition, and deliberation to account for how entrepreneurial support decisions are made. The model reflects individual and social factors that impact this decision process and provides a basis for understanding entrepreneurial support decisions across diverse actors and contexts.